The role of music in early literacy learning: a kindergarten case study - Curtis, Laurie J. (Kansas State University, 2007)
With the implementation of the No Child Left Behind Act of 2001 (PL 107-110) many pedagogical practices for literacy learning have been re-examined to align themselves with the results of the National Reading Panel report (2000). The federally funded Reading First initiative mandates systematic and explicit instruction of the key components identified by the National Reading Panel report (phonemic awareness, phonics, fluency, vocabulary, and comprehension). Higher accountability and high stakes testing has caused reflection regarding how instructional time is spent in classrooms. This qualitative case study was conducted in a combined setting of a kindergarten classroom and music education classroom in a small mid-western community over a period of nine weeks, from February 15 through April 23, 2007. This study, framed in the socio-cultural theory of constructivism (Vygotsky, 1978) and Gardner’s Theory of Multiple Intelligence (2004) explored the way a kindergarten teacher and music educator provided literacy learning opportunities for young children. Data were collected through detailed observational fieldnotes, interviews of the kindergarten teacher and music educator, and conversations with children. Data analysis revealed five characteristics that framed the literacy learning environment which included: 1) providing a caring community; 2) use of conversations; 3) connections to prior knowledge and community; 4) collaboration; and 5) consistency. Pedagogical commonalities were found to include: 1) a gradual release of responsibility; 2) use of metacognition; 3) a sharing of quality children’s literature; 4) purposeful oral language development; and 5) use of active engagement in learning, especially the use of gesturing. Data also revealed evidence of support of six components of early literacy learning: 1) phonemic awareness; 2) phonics; 3) fluency; 4) vocabulary; 5) comprehension; and 6) concepts about print. Data identified that the classroom teacher provided more incidences of instruction coded as phonemic awareness, phonics, and comprehension; with the classroom music educator providing more evidence of coded events for fluency and vocabulary learning. Analysis of combined events identified a balance of instructional methods, experiences, and techniques identifying the critical importance of the elementary music educator’s role in supporting early literacy learning of young children and the importance of collaboration in meeting needs of children.
Keywords: Early literacy; Music; Kindergarten; Reading; Education, Early Childhood (0518)